2001
DOI: 10.1159/000057002
|View full text |Cite
|
Sign up to set email alerts
|

Centromere and telomere redistribution precedes homologue pairing and terminal synapsis initiation during prophase I of cattle spermatogenesis

Abstract: Alterations in nuclear topology associated with meiotic chromosome pairing were studied in premeiotic cells and spermatocytes I of adult bovine males. To this end, we performed FISH with chromosome, pericentromeric satellite-DNA and telomere-specific probes in combination with immunostaining of synaptonemal complex proteins (SCP3, SCP1) on testis tissue sections. Nuclei of premeiotic cells (spermatogonia) exhibited a scattered telomere distribution while pericentromeres formed a few intranuclear clusters. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
(68 reference statements)
4
26
0
Order By: Relevance
“…Meiosis induction in the diploid SK1 strain and the tetraploid SK1 strain derived therefrom revealed that prophase I progression, bouquet formation and meiotic divisions were delayed in tetraploid meiosis compared with diploid wild-type meiosis -which contrasts with the situation in diploid versus allopolyploid plants (Martinez-Perez et al, 2000;Moore, 2002) and indicates that accelerated prophase I progression in polyploid plants is not a universal feature that extends to other kingdoms. Besides other possibilities, the prophase I delay in the polyploid yeast is in agreement with the assumption that a genome with increased chromosome number will require a more elaborate and time-consuming homologue search during prophase I (Dorninger et al, 1995;Pfeifer et al, 2001). How, then, according to such a scenario, is prophase I progression accelerated in polyploid plants?…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Meiosis induction in the diploid SK1 strain and the tetraploid SK1 strain derived therefrom revealed that prophase I progression, bouquet formation and meiotic divisions were delayed in tetraploid meiosis compared with diploid wild-type meiosis -which contrasts with the situation in diploid versus allopolyploid plants (Martinez-Perez et al, 2000;Moore, 2002) and indicates that accelerated prophase I progression in polyploid plants is not a universal feature that extends to other kingdoms. Besides other possibilities, the prophase I delay in the polyploid yeast is in agreement with the assumption that a genome with increased chromosome number will require a more elaborate and time-consuming homologue search during prophase I (Dorninger et al, 1995;Pfeifer et al, 2001). How, then, according to such a scenario, is prophase I progression accelerated in polyploid plants?…”
Section: Discussionsupporting
confidence: 78%
“…This is probably related to the fact that the homologue search and alignment process and the correction of non-homologous premeiotic centromere associations in polyploid plants takes place prior to the onset of meiotic prophase (Martinez-Perez et al, 2001). By contrast, the redistribution of pericentromeric heterochromatin (centromeres) in mammals and yeast occurs during the onset of first meiotic prophase (Hayashi et al, 1999;Pfeifer et al, 2001;Scherthan et al, 1996;Trelles-Sticken et al, 1999). Therefore, the elaborate architectural changes in the diploid meiocyte nucleus that occur after the initiation of meiosis probably extend the time required for the transit though prophase I, whereas the rapid prophase I progression in polyploid plants obviously benefits from the premeiotic alignment of homologous pericentromeres (Martinez-Perez et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Sycp3 commenced in preleptotene spermatocytes, identified by the presence of one or more intranuclear Sycp3 aggregates (Fig. 5A), which have been shown to mark the onset of prophase I in male germ cells in mouse and cow (Scherthan et al, 1996;Pfeifer et al, 2001). In zebrafish spermatocytes at the leptotene stage, the Sycp3 signals were detectable as short fine threads, starting from one side of the nucleus with a distinct polarity (Fig.…”
Section: Spermatocytes From Mutant Testes Fail To Progress Beyond Promentioning
confidence: 92%
“…Sycp3 and Ccna1 (cyclin A1) are expressed during the first meiotic division (35,39). The abundance of their transcripts was comparable in TSPY1-Figla transgenic and normal mice, indicating a similar complement of spermatocytes (Fig.…”
Section: Vol 30 2010mentioning
confidence: 97%